Current state of antimicrobial stewardship in organ transplantation in Singapore. Issue 5 (18th October 2022) - Chung, Shimin Jasmine; Liew, Yixin; Lee, Winnie Hui Ling; Kwa, Andrea Lay Hoon; Tan, Thuan Tong; Tan, Ban Hock
Abstract: Background: Antibiotic stewardship programs (ASPs) are well established in the public hospitals in Singapore, but they are not mandatory for transplant programs. Given the positive impact of ASPs in non‐organ transplant patients (improved use of broad‐spectrum antibiotics, reduced length of stay, and lower healthcare costs), stewardship principles are likely to benefit transplant recipients. Methods: We reviewed the progress made in ASPs in the Asia Pacific region as well as the progress of our ASP over the last decade since it was established. We also described how stewardship strategies have evolved for the purposes of our transplant program. Results: Currently, pressing stewardship issues for our transplant program include high antibiotic consumption, as well as the burden, morbidity, and mortality associated with drug‐resistant bacterial infections. Transplanting the model of stewardship onto a transplant program ignores the intricacies of transplant patients; the bespoke form of stewardship, "handshake stewardship", is more appropriate. Conclusion: To advance the cause of ASP in the transplant unit in Singapore, stakeholder buy‐in is key; empowering transplant physicians to be stewardship‐focused would be more sustainable in the long run. In addition, expanding our diagnostic armamentarium, optimizing existing therapeutics and multi‐disciplinary team involvement (including stakeholders from microbiology, and infection prevention teams) are vital. Abstract : Current state of antimicrobial stewardship in organ transplantation in Singapore.